Automorphisms and model-theory questions for Nilpotent matrix groups and rings - Levchuk, V. M.; Minakova, E. V. (Journal of mathematical sciences (New York, N.Y.), 2010)
Let R ’ = NT( m, S ). The purpose of this paper is to investigate elementary equivalences UT( n,K ) ≡ UT( m, S ) and Λ( R ) ≡ Λ( R ’) for arbitrary associative coefficient rings with identity. The main theorem gives the description of such equivalences for n > 4. In addition, we investigate isomorphisms and elementary equivalence of Jordan niltriangular matrix rings.